Respuesta :

For this case we must find the product of the following expression:

[tex](a + 3) (- 2a ^ 2 + 15a + 6b ^ 2)[/tex]

We apply distributive property term to term:

[tex](a + 3) (- 2a ^ 2 + 15a + 6b ^ 2) =\\-2a ^ 2 * a + 15a * a + 6b ^ 2 * a-6a ^ 2 + 45a + 18b ^ 2 =\\-2a ^ 3 + 15a ^ 2 + 6ab ^ 2-6a ^ 2 + 45a + 18b ^ 2=[/tex]

We add similar terms:

[tex]-2a ^ 3 + (15-6) a ^ 2 + 6ab ^ 2 + 45a + 18b ^ 2 =\\-2a ^ 3 + 9a ^ 2 + 6ab ^ 2 + 45a + 18b ^ 2 =[/tex]

Finally, the expression is as:

[tex]-2a ^ 3 + 9a ^ 2 + 6ab ^ 2 + 45a + 18b ^ 2[/tex]

Answeer:

[tex]-2a ^ 3 + 9a ^ 2 + 6ab ^ 2 + 45a + 18b ^ 2[/tex]